Single-cell analysis reveals immune cell abnormalities underlying the clinical heterogeneity of patients with systemic sclerosis - Hiroshi Shimagami; Kei Nishimura; Hiroaki Matsushita; Shoichi Metsugi; Yasuhiro Kato; Takahiro Kawasaki; Kohei Tsujimoto; Ryuya Edahiro; Eri Itotagawa; Maiko Naito; Shoji Kawada; Daisuke Nakatsubo; et al. (Nature Communications)
Abstract The autoimmune disease systemic sclerosis (SSc) presents with multiple organ manifestations that often complicate management strategies. To explore variations in immune cell subsets and their link to clinical heterogeneity, here we perform single-cell profiling of peripheral blood mononuclear cells (PBMC) from 21 SSc patients who never received immunosuppressive therapy. We identify a subset of EGR1 + CD14+ monocytes in patients with scleroderma renal crisis (SRC). This subset activates NF-kB signaling and differentiates into tissue-damaging macrophages, which accumulate at sites of tissue injury. Furthermore, we identify a CD8+ T cell subset with type II interferon signature in the peripheral blood and the lung tissue of patients with progressive interstitial lung disease (ILD), suggesting that chemokine-driven migration of these cells contributes to ILD progression. Thus, our single-cell analysis reveals distinct immune cell abnormalities associated with clinical organ manifestations, providing insights into tailored treatment strategies.